Upper secondary education in Mexico: School abandonment and public policies during COVID-19 - Carlos Alberto Arellano-Esparza; Ángeles Ortiz-Espinoza (Íconos, 2022)
Upper secondary education is the educational level with the highest dropout rate in Mexico. This situation had shown a steady decrease until before the 2020-2021 school year, when the effects of the COVID-19 pandemic began to manifest themselves. This article presents an exploratory analysis of school dropout at this level in Mexico, considering the effects of the pandemic and interventions through public policies that attempt to discourage it. A large part of the text is devoted to characterizing this phenomenon in terms of the multicausality identified in the literature, mediating effects, and the main ways of addressing the problem through public policy instruments that serve as a framework for analysis. Regarding methodological design, with data obtained from various sources, including the Survey for the Measurement of the COVID-19 Impact on Education 2020, descriptive statistics are presented that allow us to elaborate the interpretation of the findings on pre- and post-pandemic discontinuity in schooling. Among the main results, we find that economic issues have been the main cause for not continuing in upper secondary education, in addition to the fact that there were no strategies at this particular educational level to discourage COVID-related school dropout.